How should we respond to the emergence of plasmid-mediated colistin resistance in humans and animals?. (January 2017) - Al-Tawfiq, Jaffar A.; Laxminarayan, Ramanan; Mendelson, Marc
Highlights: This review discusses the emergence of colistin resistance through the development of new plasmid-mediated resistance genes. The presence of plasmid-mediated resistance genes in isolates from food animals has ignited a debate around the contribution of antibiotic consumption in animals on resistant infections in humans. In this review, the emergence and transmission of colistin resistance and the potential response strategies are discussed. Summary: Objective: The widespread use of antibiotics in humans and animals has contributed to growing rates of antibiotic resistance. Previously treatable bacterial infections now require the last line of antibiotics or are untreatable. The current antibiotic of last resort for carbapenem-resistant Gram-negative bacterial infections is often colistin. Evidence for the shifting pattern of colistin resistance and how the international community should respond are discussed in this review. Methods: The literature on colistin resistance was reviewed. Results: Plasmid-mediated colistin resistance encoded by mcr-1 was first documented in China during the routine surveillance of food animals. This has been followed by similar reports across a wide geographic area, in humans, animals, and the environment. The mcr-1 gene has been reported among human isolates in 29 countries, related to environmental samples in four countries, and in food animals and other animals in 28 countries. More recently, a second gene encoding resistance, mcr-2, has been isolated from porcine and bovine  Escherichia coli . Conclusion: The emergence and horizontal transmission of colistin resistance highlights the need for heightened stewardship efforts across the One Health platform for this antibiotic of last resort, and indeed for all antibiotics used in animals and humans.